From Needs Analysis to Conceptual Design: Developing a Sport Tourism-Integrated Physical Education Framework for Contextual Learning and Physical Literacy - Handayani, Widya; Lestari, Hikmah; Cintami Lanos, Muhsana El (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze students’ needs and develop a conceptual framework for sport tourism-integrated physical education learning to enhance contextual learning, physical literacy, and student engagemen. Method: A mixed-methods approach was applied using a Research and Development (R&D) design based on the ADDIE model, focusing on the analysis and design stages. An exploratory sequential design was employed, where qualitative data were first collected through interviews, observations, and documentation, followed by quantitative data using questionnaires. The participants consisted of 100 physical education students and five lecturers at PGRI Palembang University, selected through purposive sampling. Quantitative data were analyzed using descriptive statistics (mean and standard deviation), while qualitative data were analyzed through thematic analysis and integrated using triangulation. Results: The findings show that students’ needs for experience-based physical education learning are generally high to very high. Contextual learning (M = 4.38), physical literacy (M = 4.53), and student engagement (M = 4.37) fall into the very high category, while sport tourism-based learning (M = 4.18) is categorized as high. Interview results reinforce these findings, highlighting the importance of real-life learning, outdoor experiences, and active student involvement. Based on these results, a conceptual model of sport tourism-integrated physical education learning was developed. Novelty: This study contributes to the development of an innovative learning framework that integrates contextual learning, physical literacy, and student engagement through sport tourism. The novelty lies in positioning sport tourism as a pedagogical approach to support meaningful and experience-based learning in physical education.